Crystallization Modalities in Polymer Melt Processing Fundamental Aspects of Structure Formation - Janeschitz-Kriegl, Hermann; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2010)
The first book to explicitly focus on the processing of crystallizing polymers, it presents innovative research on diverse interfering processes to help clarify the subject. The first to address the unexpectedly strong interaction of three transport phenomena: heat transfer, momentum transfer (rheology) with crystallization kinetics. With many applications, most well-known crystalline structures are found in polymers like high and low density polyethylene, polypropylene, polybutene and their copolymers. Common problems such as anisotropic shrinkage, warping, and split fiber formation are covered. In addition to applications on amorphous polymers, attempts at numerical simulation on crystallizing polymers are also examined. A feeling for the origins of undesired orientations and frozen-in stresses often associated with the manufacturing process is provided to polymer chemists, applied physicists, rheologists, plastics engineers, mold makers and material scientists.
Introduction -- Interaction of three transport phenomena:heat transfer, flow and crystallization kinetics; Available theories describing the crystallization process; Examples for special cases; Crystallization in confined volumina; Behaviour of confined samples; Influence of strong temperature gradients -- Kinetics and structure formation in unloaded quiescent melts;Introductory remarks; Empirical techniques; Theoretical considerations; Winter´s gel point -- Flow induced processes causing oriented crystallization; Preamble;Some comments of considerable reach; Survey of activities in the field of flow induced crystallization; Duct flow experiments; Flow induced small-sized ('point-like') nuclei; Relaxation phenomena; Uninterrupted flow treatments. Closing remarks.
Keywords: Polymers .; Physical chemistry; Chemical engineering; Industrial engineering; Production engineering; Crystallography; Mechanics; Mechanics, Applied; Polymer Sciences; Physical Chemistry; Industrial Chemistry/Chemical Engineering; Industrial and Production Engineering; Crystallography and Scattering Methods; Solid Mechanics